Patient Engagement and Co-creation in Healthcare Services: A Scoping Review - Thiruppavai Sundaramurthi; Smita Mathews; Ella Bermudez; Satish Mahajan (Patient Experience Journal)
Objective: The objective of this review was to find literature related to the concepts of patient engagement and co-creation in healthcare services and identify models and/or frameworks that combined these concepts. Methods: We developed the eligibility criteria using the Population-Concept-Context framework applicable to studies with population of patients exploring the concepts of engagement and co-creation in the context of healthcare services. The search was conducted in PubMed, CINAHL, Cochrane, APA PsycINFO, and Ovid MEDLINE. We searched for articles in English with no search limitations on publication dates. Reviewers screened abstracts and full texts to identify articles for data extraction. We developed, piloted, and implemented a data extraction tool to extract key information needed to answer the research questions. Results: Our search yielded 3632 references. Fifty-five studies were included in this review with 26 studies in patient engagement and 29 studies in co-creation. Many identified studies explored the field of healthcare services research. We identified the common principles of patient engagement and co-creation along with the existing models and frameworks that were either applied to guide these studies or proposed through these studies. Conclusion: Though there were several models describing different components and phases of patient engagement and co-creation concepts, there was a lack of unified, domain-agnostic models that described characteristics of these combined concepts. This review suggested the need for an innovative conceptual model that would bring together the concepts of co-creation and the principles of patient engagement applicable to various activities in healthcare such as research, implementation, and evaluation.